SOCIOLOGY OF TEACHING - Metz, Mary (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
In this course we will consider several overlapping perspectives through which to understand teachers and their work. We will also look at how public and researchers’ images of teaching and of teachers have shifted over the last thirty years. We will look at teaching as a career in a way that invites comparison with other careers. We will consider the school as a workplace and examine the distinctive character of the actual work of teaching as it is practiced daily and yearly. Teaching is carried out within the complex organizational context of school, school district, and state. Pressures from the federal and state levels on local districts and schools are changing rapidly. As a foundation for understanding these rapidly evolving pressures and their effects, we will look at the organizational characteristics of schools in conversation with the needs and demands of teaching as work. This understanding of the fundamental social characteristics of teaching in organizational context is critical to understanding not just the present moment but the past and the future of teaching.